Prosthetic Replacement of the Ocular Surface Ecosystem for Limbal Stem Cell Deficiency: A Case Series. Issue 12 (12th December 2022) - Garg, Anubhav; Trinh, Tanya; Wong, Bryan M.; Mimouni, Michael; Ramdass, Stephanie; Liao, Jennifer; Chandrakumar, Manokaraananthan; Slomovic, Allan R.; Chan, Clara C.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To assess outcomes of limbal stem cell deficiency (LSCD) in patients treated with Prosthetic Replacement of the Ocular Surface Ecosystem (PROSE). Methods: Retrospective case series. Patients with LSCD who received PROSE treatment were included. Data including best-corrected visual acuity (BCVA) and LSCD staging before and after PROSE dispensing were collected to characterize each case. Results: Five eyes of four patients were included. All patients were female, with an age range of 21 to 80 years. Each patient received a PROSE device with diameters ranging from 16 to 18.5 mm. Follow-up ranged from 11 to 29 months. Tolerated wear times ranged from 3.5 to 10 hr daily. Four eyes showed improved BCVA and unchanged LSCD staging as per the global consensus after PROSE treatment. Three of these eyes had stage 3 and one had stage 1C LSCD at diagnosis. The fifth eye had worse BCVA and recurrence of stage 3 LSCD post–living-related conjunctival limbal allograft transplant despite PROSE treatment. Conclusions: Prosthetic Replacement of the Ocular Surface Ecosystem may be a viable treatment for LSCD, including severe cases, because it can provide symptom relief and improve vision. Its customizability, as demonstrated in this study, is beneficial for troubleshooting issues with fitting. Future studies are needed to further assess PROSE as treatment for LSCD.